Psyche : a novel - Young, Phyllis Brett (McGill-Queen's University Press, 2008)
"A child who is the very centre of her parents' life is torn away in the darkness and left to grow up in the hostile hills of the north country. Recognizing that the couple who raised her have nothing more to offer, she leaves with an artist who initiates her into adulthood. "Psyche" is the gripping story of a wealthy urban mother's anguish and powerlessness when her child is kidnapped and the abandoned child's remarkable resilience as she ultimately finds redemption through art, education, and psychology. This 1959 international bestseller by Canadian writer Phyllis Brett Young focuses on issues of character and environment in an unconventional coming of age story that draws the reader into an exploration of the decidedly modern themes of kidnapping, sexual assault, and the sex trade industry."--Book cover.